Akulturasi dan Kearifan Lokal dalam Tradisi Baayun Maulid pada Masyarakat Banjar - Jamalie, Zulfa (UIN Maulana Malik Ibrahim Malang, 2014)
This research examines the acculturation and transformation of traditional values of Banjarese Baayun Maulud . It used religious anthropology approach as an effort to understand the deepest meaning of the research object. The result shows that this tradition was historically started from swinging child ceremony of Dayakese Tribe in Kalimantan, in order to give blessing, give name, pray for safety, and to thank for the child birth. A long with the incoming and development of Islam in this region, the ceremony which was inherited by the ancestors experienced changes. The Islamic preachers have changed and acculturated this ceremony so it is full of Islamic values. The ceremony once called swinging child ceremony, then after the acculturation it became Baayun Maulud. The venue is centralized at the mosque and is combined with the celebration of Muhammad’s birthday. The children are swung with qur’an recitation, rhyme quatrains of maulud, and prayers. The local wisdoms and the religious thoughts has been unified in harmony in the tradition, which becomes the sign of gratitude expressions for the child birth, as well as for celebrating and honoring the birth of the Greatest Prophet Muhammad. Penelitian ini mengkaji akulturasi dan transformasi nilai dalam tradisi Baayun Maulid masyarakat Banjar. Penelitian ini menggunakan pendekatan antropologis keagamaan sebagai upaya memahami makna mendalam dari objek penelitian. Hasil penelitian menunjukkan bahwa sejarah munculnya tradisi ini bermula dari upacara maayun anak masyarakat Dayak Kalimantan untuk memberikan keberkahan, memberi nama, menyampaikan doa keselamatan, dan tanda syukur atas kelahiran anak. Seiring dengan masuk dan berkembangnya Islam di kawasan ini, upacara yang diwariskan oleh nenek moyang ini pun mengalami perubahan. Ulama penyebar Islam telah merubah dan mengakulturasi upacara ini menjadi sarat dengan nilai-nilai keislaman. Apabila semula upacara ini dinamakan Baayun Anak, maka sesudah diakulturasi berubah menjadi Baayun Maulid. Tempat pelaksanaan dipusatkan di masjid dan disandingkan dengan peringatan maulid Nabi. Anak diayun dan dibacakan al Quran, syairsyair maulid, serta doa. Tradisi lokal dan ajaran agama telah bersatu secara harmonis dalam kegiatan Baayun Maulid, yang menjadi penanda kesyukuran atas kelahiran anak sekaligus peringatan dan penghormatan atas kelahiran Nabi Muhammad.